Profile of Early Childhood Education Services and Students’ Nutritional Status: Designing an Integrated Stunting Intervention Model - Mukminin, Amirul; Bintari, Siti Harnina; Kasmini Handayani, Oktia Woro; Ambari Sumanto, Reni Pawestuti; Waluyo, Edi (International Journal of Child Health and Nutrition, 2026)
Background: Stunting management in Semarang City remains sectoral and has yet to involve early childhood education centres. This study investigates early childhood education services, nutritional status, and the impact of services on stunting prevalence and designs a stunting intervention model. Methods: A cross-sectional survey was conducted to collect data from 314 integrated early childhood education centres in Semarang City, with 20 selected for anthropometric data collection. Nutritional status was classified as wasting, stunting, and underweight. Dummy variable regression analysis was used to determine the impact of services on stunting prevalence. Results: The integrated early childhood education (IECE) was considered good in 55.97% of cases, while 44.03% were rated as less satisfactory. The prevalence of stunted students (29%) was the highest, followed by underweight and wasting. The prevalence of stunting was higher among male students than female students, and the rate of stunting in boys increased with age. Although the influence of early childhood education services on stunting reduction was found to be very weak, it remains a positive factor in lowering stunting prevalence. Enhancing the quality of IECE through an integrated intervention model, especially targeting nutrition and health among young children, represents a significant opportunity to implement effective non-medical interventions to reduce stunting, as evidenced by service-delivery rates. Conclusion: IECE service was found to be effective in reducing the prevalence of student stunting. These findings imply an urgent need for coordinated, targeted actions that leverage existing policy frameworks to improve service quality and focus interventions on the most vulnerable groups.